The Perception of 5th Semester English Students on Watching English Movies to Enhance Listening Skill at Universitas Nias - Marinus Zai; Theresia Trines Anjelin Zai; Elnardus Fransiskus Jafrinus Namo; Juardiman Putra Gea; Yofita Gulo; Erna Zamasi; Yaredi Waruwu (Journal on Education, 2025)
This study investigates the opinions of Universitas Nias fifth-semester English students about using English-language movies to improve their listening skill. Numerous studies have demonstrated that seeing movies can help students learn vocabulary, pronounce words correctly, and understand other accents. But few research has explicitly examined how students view this approach. Focus group discussions (FGDs) and structured interviews with 14 participants were used to gather data for this study, which uses a qualitative descriptive methodology. Key themes in the students' answers were found through the application of thematic analysis. The results show that students view English-language movies as a useful resource for enhancing their listening skill, particularly when it comes to recognizing various accents and genuine speech patterns. But obstacles like frantic conversations, strange vocabulary, and the need for subtitles continue to impede their development. According to the study, the learning process can be maximized by choosing relevant movies, progressively cutting back on the use of subtitles, and incorporating discussions. These results advance our knowledge of audiovisual learning techniques and offer suggestions to teachers on how to create engaging listening lessons.